Um Colar Para Nanã: um manuscrito cartográfico para o não esquecimento - OLIVEIRA, Patrick Garcês de (2019)
This manuscript is the poetic document of the creative process of the theater play A necklace to Nanã, where I have my own cartographic method, which I call “the Cartographic Manuscript”, and use it as a way to rescue my memories and experiences, transforming them into matter genesis and poetic power in the construction of my work. In this process, I divide the writing of my manuscript into five moments: clues, the map, first water skin, second water skin and third water skin. Each of these moments designates a fragment of the work that together, unified, serve as notes for paths that can be traversed within the theater.